Understanding the Safeguarding Role of Forest Resources and Its Determinants During the COVID-19 Pandemic: Insights from Vietnam, Laos, and Cambodia - Kien, Nguyen Duc; Dinh, Nguyen Cong; An, Le Thanh (Forest and Society, 2024)
Sustainable forest management can play a vital role in building resilient economies and communities that can withstand pandemics, climate change, and other global challenges. Through a comprehensive analysis of local communities surrounding protected areas, we examine the extent of forest reliance for livelihoods and identify key drivers behind changes in forest-resource use during the pre-pandemic in 2019 and post-pandemic in 2022. The study's findings reveal a noteworthy increase in the proportion of land utilized for livelihood activities, especially for production forests, in study sites between 2019 and 2022. Local communities still heavily rely on forest resources for their livelihoods, with a significant increase in household income derived from forest-based activities between 2019 and 2022, approximately 112.1%, 28.7%, and 1.68% for Vietnam, Cambodia, and Laos, respectively. Additionally, the study highlights an upsurge in forest dependence during the pandemic period, emphasizing the importance of forests in safeguarding the economies of forest-dependent communities. Findings also shed light on the determinants of forest dependence changes amid the pandemic, including income from forests, poverty status, minority group status, and receipt of COVID-19 relief. These results provide valuable insights into the relationship between forest resources and rural livelihoods for promoting sustainable forest management and safeguarding the well-being of local communities in the face of future challenges.